Wednesday

July 23, 2014

July 23, 2014

Posted by **Amie** on Saturday, March 12, 2011 at 10:37pm.

- calculus -
**Reiny**, Sunday, March 13, 2011 at 12:17amdy/dx = (2/3)(9-x^2)^(-1/3) (2x)

when x = 1, y = 8^(2/3) = 4

dy/dx = (2/3)(8)^(-1/3) (2)

= (4/3)((1/2) = 2/3

equation:

y = (2/3)x + b

at( 1,4)

4 = (2/3) + b

b = 10/3

y = (2/3)x + 10/3

**Related Questions**

calculus - consider g(x)= {a sin x + b, if x ≤ 2pi} {x^2 - pi x + 2, if x...

College Calculus - Let f(x) = 3x^2 - 2x + 1 a) write an equation of the line ...

Tangent Lines-Calculus - a line is tangent to the curve y= (x^2 + 3)/ (x+3)^1/2 ...

Calculus - Find the slope of the tangent line to the curve y = (x^2 -8)^6 at x...

calculus - 5. Let f be the function given by f(x) = x3- 7x + 6. a. Find the ...

Calculus - Please help this is due tomorrow and I dont know how to Ive missed a ...

calculus - Write the equation of the tangent line to the curve at the indicated ...

CALCULUS HELP - Write the equation of the tangent line to the graph of the ...

calculus - find the equation of a quadratic function whose graph is tangent at x...

calculus - I'm feeling pretty stupid right now because I can't remember how to ...